Influence of distinctive Japanese culture on doing business for American companies - Moroz, Olha; Olšanová, Květa; Neumannová, Pavla; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
The actuality of chosen topic for the thesis results from the fact that Japan is third largest economy in the world which population of 127 million people that puts this country on 11th place in the world ranking. Japan is the country with high GDP, is 9th most competitive country in the world and 14th most innovation driven country. Economic, political, social and technological environments stress attractiveness of Japan for American companies. But, due to different cultures, failures of US companies are very common and this was the interest behind chosen topic. The practical part deals specifically with understanding of cultural differences between countries using Hofstede cultural dimensions, applying results of analysis to Wal-Mart case and providing recommendations to US companies on what that should take into account when entering Japanese market. The methodological tools used in this thesis include secondary research, case study method and 7 Ps model created by author in order to provide recommendations covering main obstacles created by distinctive culture. Secondary research is used to analyze the existing information required to complete the theoretical part of the analysis and partly practical. Case study method was used in order to analyze obstacles Wal-Mart faced on Japanese market and give recommendations.
Vedoucí práce: Květa Olšanová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses